Reduksi Limbah Jerami Dan Sekam Padi Sebagai Pakan Ternak Alternatif - Andi Muhamad Iqbal Akbar Asfar*; Andi Muhammad Irfan Taufan Asfar Asfar; Ridwan Ridwan; Jeanne Dewi Damayanti; Muh Iqbal Mukhsen (Universitas Lancang Kuning, 2023)
The quantity of straw and rice husk waste remains a crucial problem to be solved, especially in Maggenrang Village, Bone Regency, South Sulawesi, so an alternative way for farmers to reduce it is through the combustion process that will add the problem of the impact of temporary air pollution but is harmful to the health of other residents. Therefore, community service is carried out to provide innovative solutions to the Eccengnge’ Farmer Group in Maggenrang Village by transforming rice straw and husk through the delignification process, which is continued by making animal feed pellets. The method of implementing this activity is carried out with three main stages: counseling, training, and mentoring to partners. The results showed an increase in partners' skills with three evaluation components, namely knowledge with a rise of 90% and production and supporting skills with an increase of 90% and 80%. Increasing skills for partners provides potential business opportunities by adding value to straw and rice husk waste into products with high commercial value, thus supporting the fulfillment of alternative, independent feed by the Maggenrang Village government based on local potential.